Facies Analysis and Depositional Environment of the Sarvak Formation (Cenomanian) in the Zagros Basin (SW of Iran) - Afghah, Massih; Fadaei, Hamid Reza (Challenging Issues on Environment and Earth Science Vol. 3, 2021)
In this study, two stratigraphic sections of Sarvak Formation were selected which are nominated Bavan and Kherameh sections. Over 379.5 meters of the Sarvak Formation and 260 thin sections have been studied. Index microfacies and foraminifers have been identified. Index microfacies include Boundstone, Wackestone and Packstone. The frequency of bioclast has been determined as larger that of the other microfacies elements. Based on the type and abundance of skeletal and nonskeletal grains and type of matrix, 14 sublithofacies have distinguished in 3 depositional environments which are include 1) Lagoon 2) Reef 3) Open marine. The mentioned determined microfacies were deposited in a Carbonate Platform of Homoclinal Ramp. Based on micropalentological data, the age of the Sarvak Formation is assigned to Cenomanian.